A survey on prevalence and risk factors of Varroasis in West Azerbaijan, Iran. Issue 4 (4th July 2018) - Bahrami, Milad; Mohammadzadeh, Davood; Emami, Seyyed Jamal; Rabiee, Mohammad Hasan; Bokaie, Saied
ABSTRACT: Varroa destructor is considered one of the major threats for apiculture worldwide. The present study was designed to identify risk factors associated with V. destructor occurrence in West Azerbaijan, Iran. During autumn 2016, data on general apiary traits, occurrence of Varroasis, management practices, and treatment procedures were recorded in 174 apiaries using a questionnaire in a cross-sectional study. In total, 74% of apiaries reported infestation with varroa mites. Based on results of logistic regression models, management by semi-experienced (5–10 years) and experienced (>10 years) beekeepers (odds ratio (OR) = 0.058, 95% confidence interval (CI) = 0.008–0.413, p  = 0.004, and OR = 0.048, 95% CI = 0.010–0.225, p  < 0.0001, respectively), using a guard wall (OR = 0.0928, 95% CI = 0.333–0.258, p  < 0.0001) and located in >6 km distance to cities and/or motorways (OR = 0.280, 95% CI = 0.084–0.934, p  = 0.038), were found to decrease the risk of varroa infestation. Apiaries using traditional hives were associated with increased risk of varroa infestation compared to modern hives (OR = 5.346, 95% CI = 1.614–17.698, p  = 0.006). Anti-varroa treatments were applied in 95% of the studied apiaries. Synthetic acaricides such as fluvalinate, flumethrin, and amitraz showed a better anti-varroa effect when used in combination with organic acaricides such as thymol and formic acid ( p  < 0.05). Continued epidemiological studies are recommended for final control of disease.